2007
DOI: 10.1007/s00428-007-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis of the lung: case report and review of the literature

Abstract: Human brucellosis is a worldwide re-emerging zoonosis. However, its histological appearance has only been occasionally described. We report the case of a young girl who had been suffering from a spontaneous fracture of the eighth thoracic vertebra at the age of 7. At the age of 15, X-ray showed a translucence of the seventh and ninth thoracic vertebra, and additionally, a bi-lateral episcleritis was detected. Three months later, she was admitted to the hospital because of perspiration at night and moderate fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Histological findings in pulmonary brucellosis cases vary, and the vast majority of information available in the literature is associated with chronic cases, but our data are consistent with the limited amount available, i.e. that inflammation is often lymphohistiocytic and/or neutrophilic (Theegarten et al , 2008). We did not observe progression to granulomatous inflammation, presumably because of the short duration of the study.…”
Section: Resultssupporting
confidence: 87%
“…Histological findings in pulmonary brucellosis cases vary, and the vast majority of information available in the literature is associated with chronic cases, but our data are consistent with the limited amount available, i.e. that inflammation is often lymphohistiocytic and/or neutrophilic (Theegarten et al , 2008). We did not observe progression to granulomatous inflammation, presumably because of the short duration of the study.…”
Section: Resultssupporting
confidence: 87%
“…Histological findings of brucellosis in chronic cases includes abscesses, granulomatous lesions (caseating or non-caseating) and non-specific inflammation (Ahmed et al, 2012). Grossly, granulomatous lesions and edema were observed in lungs in the present study, these types of lesions have been reported in humans (Theegarten et al, 2008). Clinical signs and macroscopic lesions are contrary to those reported earlier by Nasruddin et al (2014) in experimentally infected bucks with Br.…”
Section: Discussioncontrasting
confidence: 90%
“…In humans, respiratory impediments are mostly mild flu-like with sore throat and mild dry cough. May cause pneumonia and lung abscess whereas serious manifestations are rare (Theegarten et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is the most prevalent zoonotic disease worldwide, causing spontaneous abortion and fetal death in animals and severe flu-like symptoms, focal complications, and often, chronic disease in humans (7,11,22,27,40,41,49,50). Brucella species are typically transmitted to humans through consumption of unpasteurized dairy products or exposure to fluids or tissues from infected animals (45,49).…”
mentioning
confidence: 99%